Shakespearean tragedy and the internet-disseminated short film: adaptations of Hamlet and Romeo and Juliet on YouTube and Vimeo - Crouch, Makenzi Ilse (2017)
Significant changes and advances in technology in the twenty-first century, and the rapid evolution and development of the internet in particular, have shaped the production, publication, and consumption of, and access to, a wide range of media. For adaptors of Shakespeare, such advances can be exploited as new and innovative ways through which to interpret, perform, and understand Shakespeare. This thesis argues that a possibility space emerges from the restrictions of video-sharing sites such as YouTube and Vimeo, enabling the creation and online distribution of original internet-disseminated short film adaptations of Shakespeare on a scale — and with a potential audience — previously unimaginable to those without significant financial resources. I explore the effect that the enforced brevity of the possibility space has on filmmakers’ adaptations of Shakespeare and ask how this space enables newly creative and innovative approaches to adapting Hamlet’s ‘to be or not to be’ speech, Ophelia’s image (and death), and a distilled Romeo and Juliet narrative. I aim to show that a generally circulated cultural memory of Hamlet and Romeo and Juliet is crucial for this kind of short-form adaptation, as the brevity of the format relies on audience familiarity with the images and texts deployed to fill in any gaps. I demonstrate that image-based adaptations, such as Ophelia’s death, are predominantly reductive due to a strong visual tradition that results in repeated reproduction of the same image, whereas text-based adaptations, such as Hamlet’s speech, allow exploration and amplification due to the nebulous nature of the text and exploitation of the possibilities of film; the Romeo and Juliet love story, bound up in both text and image, is more visually resonant than adaptations of Hamlet’s speech, but less so than those of Ophelia’s death. Ultimately, I conclude that although the possibility space always exists, it is not always leveraged in the same way: it can, and does, offer internet-disseminated short filmmakers the opportunity to approach familiar Shakespearean material in new and innovative ways, but this creative potential can be overlooked in favour of static, mimetic replication that uses Shakespeare to confer legitimacy without writing back.